The Non-Aesthetic Aspect of Mangkunagaran-Style Dance: Study From The Perspective of Social Context (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2020)
This study aims at analyzing the non-aesthetic aspect of Mangkunagaran-style dance from the perspective of its social context. The method employed in the study is interpretative-descriptive qualitative. The approach used social culture to analyze the perspectives. The research was conducted in Pura Mangkunagaran, with the focus of research lies on the non-aesthetic aspect of Mangkunagaran-style dance taken from the perspective of its social context. Techniques for collecting data was an observation, interview, and documentation study. The data validity mainly used data triangulation. Results show that from the perspective of social context, the Mangkunagaran-style dance is divided into four major social functions, i.e., the social order for integration, the function of expression, the function of entertainment, and the function of Psychiatric, Aesthetic, and Economic. These for main social functions are taken part in the existence of Mangkunagaran-style dance in Pura Mangkunagaran and wider communities.